PVDOMICS: A Multi-Center Study to Improve Understanding of Pulmonary Vascular Disease Through Phenomics. Issue 10 (27th October 2017) - Hemnes, Anna R.; Beck, Gerald J.; Newman, John H.; Abidov, Aiden; Aldred, Micheala A.; Barnard, John; Berman Rosenzweig, Erika; Borlaug, Barry A.; Chung, Wendy K.; Comhair, Suzy A.A.; Erzurum, Serpil C.; Frantz, Robert P.; et al.
Abstract : Supplemental Digital Content is available in the text.